Philosophy of Behavioral Biology - Kathryn S. Plaisance; Thomas A.C. Reydon (Springer, 2012)
This volume offers a broad overview of central issues in the philosophy of behavioral biology, addressing philosophical issues that arise from the most recent scientific findings in biological research on behavior. It thus exemplifies an approach to philosophy of science that is scientifically informed as well as interdisciplinary. Accordingly, it includes chapters by professional philosophers and philosophers of science, as well as practicing scientists.